More open - better governed? Evidence from high- and low-income countries - Andreas Bergh; Irina Mirkina; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2013)
Using World Bank data on institutional quality and the KOF Globalization Index, we examine over 100 countries from 1992 to 2010 to analyze the relationship between economic and social globalization and six measures of institutional quality. Theoretically, the incentives of elites to respond to globalization by improving institutions should differ between low-income and high-income countries. Empirically, increasing economic flows and social globalization are followed by improving institutions in rich countries, while the effect is the opposite for low-income countries. Previous findings of positive effects of trade on institutional quality are likely driven by rich countries.
Keywords: H83; F63; O11; 330; globalization; institutional quality; developing countries